EFFECT OF PLANTING SCHEME AND BIOSTIMULANT RATE ON THE FORMATION OF LEAF OF FODDER BEET (UZBEKISTAN-83) - Yuldasheva Zulfia Kamalovna; Mamatdurdiyev Ulugbek Firnafas ugli (Western European Studies, 2023)
This article proves that the planting scheme and biostimulant rate have a positive effect on the formation of ball leaves of the fodder beet (Uzbekistan-83) variety. 70x25-2 and Tandem biostimulator were used at different rates, and Fitovak biostimulator was studied as an etolon for this biostimulator. Tandem biostimulator at a low rate of 0.4 liters per hectare led to an increase in the number of leaves, while Fitovak It has been proven that biostimulant (etolon) shows high performance when applied at the rate of 300ml/ha.
Keywords: Beetroot; biostimulant; norm; seed